Illicit Financial Flows, Extractive Sectors, and the Energy Transition: Building State Capacity to Finance the SDGs - Philippe Le Billon (Revue Internationale de Politique de Développement)
States play a crucial role in the capture and allocation of commodity revenues shaping development outcomes. This chapter examines their capacity to address illicit financial flows and better finance development programmes, focusing on energy transition revenues. It first reviews the main findings about state capacity to harness commodity revenues to reach key Sustainable Development Goals. It then explores the complex interplay between state capacity, commodity-based financial flows, and development processes in the context of the energy transition. Highlighting the diversity of state capacities among commodity-dependent countries and possible energy transition trajectories, the chapter discusses opportunities and challenges resulting from changes in the volume, type and price volatility of commodities, and associated illicit financial flows associated with the energy transition. State capacity must anticipate and respond to shifts in dependence on fossil fuels to energy transition minerals and renewable energy production in order to avoid repeating illicit financial flow patterns associated with the ‘resource curse’ and poor development outcomes.